2021
DOI: 10.3390/healthcare9070899
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiovascular Risk Using Nonalcoholic Fatty Liver Disease Scoring Systems

Abstract: This study aimed to determine whether nonalcoholic fatty liver disease (NAFLD) is an independent risk factor for CVD and to identify the most useful NAFLD diagnostic tool for predicting CVD. Data from a total of 23,376 Korean adults without established CVD were analyzed. Cardiovascular risk was calculated using the Framingham Risk Score (FRS) 2008. The presence of NAFLD was defined as moderate-to-severe fatty liver disease diagnosed by ultrasonography. Scores for fatty liver were calculated using four NAFLD sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Indeed, elevated C-reactive protein levels are associated with CVD risk in MASLD [73] , but the pro-inflammatory, insulin-resistant and hypertriglyceridemic components of NAFLD are generally neglected by available CVD risk scoring systems which, additionally, need to be locally validated [74] . Consistent with this concern, a Japanese study conducted among subjects with T2D and suspected coronary artery disease found that NAFLD, in addition to coronary artery calcium scores and FRS, improved the risk classification of cardiovascular events [75] . Similarly, a Korean population study found that the severity of steatosis diagnosed with ultrasound and NAFLD scoring systems correlated with increased CVD risk [76] .…”
Section: Current Strategies For Cardiovascular Risk Assessments In Masldmentioning
confidence: 76%
“…Indeed, elevated C-reactive protein levels are associated with CVD risk in MASLD [73] , but the pro-inflammatory, insulin-resistant and hypertriglyceridemic components of NAFLD are generally neglected by available CVD risk scoring systems which, additionally, need to be locally validated [74] . Consistent with this concern, a Japanese study conducted among subjects with T2D and suspected coronary artery disease found that NAFLD, in addition to coronary artery calcium scores and FRS, improved the risk classification of cardiovascular events [75] . Similarly, a Korean population study found that the severity of steatosis diagnosed with ultrasound and NAFLD scoring systems correlated with increased CVD risk [76] .…”
Section: Current Strategies For Cardiovascular Risk Assessments In Masldmentioning
confidence: 76%
“…In the original publication of DSI [18], the authors mentioned that DSIespecially the higher risk thresholdscould be used as a diagnostic surrogate for NAFLD in epidemiologic studies, similar to other NAFLD indexes like HSI [27][28][29][30][31][32], FLI [27,[33][34][35][36][37][38][39][40][41][42] and LFS [43]. However, this claim should be confirmed in the context of large-scale epidemiological studies in relation to major outcomes such as cardiovascular diseases, type 2 diabetes, liver cancer, or mortality [44].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, although the waist circumference is a mandatory factor for the MS diagnosis according to the IDF [1], it is not considered in any CV risk calculation tool, which may be important, especially in patients with metabolic syndrome. On the other hand, scores from non-alcoholic fatty liver disease (NAFLD) scoring systems like the Fatty Liver Index (FLI), which are strongly associated with high CVD risk [34], do include waist circumference in their calculation [35]. BMI is a required parameter when calculating 10-year cardiovascular risk using the DIAbetes Lifetime perspective (DIAL) model.…”
Section: Discussionmentioning
confidence: 99%